2020
DOI: 10.15562/ism.v11i1.666
|View full text |Cite
|
Sign up to set email alerts
|

Efek pemberian ekstrak etanol bawang putih (Allium sativum) sebagai hepatoprotektor pada tikus putih jantan galur wistar (Rattus norvegicus) yang diinduksi parasetamol dosis hepatotoksik

Abstract: Garlic (Allium sativum) is a plant that known to have various properties that can be used in treatment as a hepatoprotective agent. This study aim was to determine the effect of garlic ethanol extract (Allium sativum) in Wistar strain white male rats (Rattus norvegicus) which was induced by paracetamol in hepatotoxic dose. This research is an experimental study with randomized the post-test only control group design with sample consisted of twenty-four Wistar strain white male rats (Rattus norvegicus). The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Garlic extract at a dose of 500 mg/kgBW is the optimal dose in this study. This is in accordance with previous studies which showed that garlic extract was able to accelerate the regeneration of hepatocytes so that no further damage occurred (Harsa, 2020).…”
Section: Resultssupporting
confidence: 93%
“…Garlic extract at a dose of 500 mg/kgBW is the optimal dose in this study. This is in accordance with previous studies which showed that garlic extract was able to accelerate the regeneration of hepatocytes so that no further damage occurred (Harsa, 2020).…”
Section: Resultssupporting
confidence: 93%